Improvement of alcohol distillation plant operation - Bulii, Yurii (My University, 2024)
The criteria for improving the operation of distillation plant include the degree of purification of rectified alcohol from impurities, the consumption of vapor, hot process water for hydroselection, and cooling water. The aim of research was to study the effectiveness of innovative ways to improve the operation of distillation plant: carrying out the processing of alcohol-containing fractions and epuration of beer distillate in cyclic mode, the recirculation of distillation residue of rectification and ether columns, impurity concentration column and extractive rectification column, as well as of the method which provides for the supply to the impurity concentration column of power in a vaporous state.

Критеріями підвищення ефективності роботи ректифікаційної установки є ступінь очищення спирту-ректифікату від домішок, витрата пари, гарячої технологічної води на гідровідбір, охолоджувальної води. Метою дослідження було вивчення ефективності інноваційних способів удосконалення роботи ректифікаційної установки: проведення переробки спиртовмісних фракцій та очищення пивного дистиляту в циклічному режимі, рециркуляції ректифікаційного залишку ректифікаційної та ефірної колон, колони збагачення домішок та колони екстрактивної ректифікації, а також способу, що передбачає подачу до колони збагачення домішок енергії в пароподібний стан.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; alcohol; distillation; rectification; impurities; hydroselection; дистиляція; ректифікація; домішки; гідроселекція